2010
DOI: 10.1007/s10453-010-9171-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to airborne microorganisms, hyphal fragments, and pollen in a field of organically grown strawberries

Abstract: Many working environments are predisposed for larger than average amounts of fungi and other microorganisms often due to organic material being handled. From 2003 to 2007, the area used for strawberry production in Denmark increased by 62%. The purpose of this study was to determine the levels of exposure to microorganisms, endotoxin, (1?3)-b-D-glucan (b-glucan), and pollen in a field of strawberries. The study was carried out in eastern Denmark from the middle of June to the beginning of August 2008. The stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
(53 reference statements)
1
11
4
Order By: Relevance
“…In this study, we have found a seasonal variation in outdoor b-glucan exposure with the highest concentrations in spring and summer. A variation in b-glucan is also found in a strawberry field during an eight-week period in the summer (Tendal and Madsen 2010). Seasonal variations in indoor concentrations of b-glucan have not been measured earlier, but in studies of airborne fungi (Shelton et al 2002) and pollen (Tormo-Molina et al 2009) in buildings and outdoor environments in the United States and Spain, it was found that outdoor levels of exposure to pollen and culturable fungi has an important influence on indoor exposure to pollen and culturable fungi.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, we have found a seasonal variation in outdoor b-glucan exposure with the highest concentrations in spring and summer. A variation in b-glucan is also found in a strawberry field during an eight-week period in the summer (Tendal and Madsen 2010). Seasonal variations in indoor concentrations of b-glucan have not been measured earlier, but in studies of airborne fungi (Shelton et al 2002) and pollen (Tormo-Molina et al 2009) in buildings and outdoor environments in the United States and Spain, it was found that outdoor levels of exposure to pollen and culturable fungi has an important influence on indoor exposure to pollen and culturable fungi.…”
Section: Discussionmentioning
confidence: 90%
“…We found exposures in towns to be between 1.2 ng m -3 and 65.8 ng m -3 . In a strawberry field using stationary sampling and exactly the same extraction methods as used in this study, the b-glucan concentration (n = 12) ranged from 9.3 ng m -3 to 170 ng m -3 (median = 44.0 ng m -3 ) (Tendal and Madsen 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to spores, particles smaller than fungal spores are shown to be aerosolized from fungal cultures (16,28,37). These particles are referred to as fungal microparticles (measured sizes between 0.3 and 1.3 m in d a ) (37), fungal fragments (measured sizes between 0.3 and 1.5 m in optical diameter) (16), or fungal hyphal or conidial fragments (sizes not measured) (18) and can constitute a large part of bioaerosols in terms of numbers (16,18,36,52).The aerodynamic diameter (d a ) of an airborne particle influences the site of deposition in the respiratory system and the possible health effects it can cause (10, 22, 23), as well as its ability to stay airborne and to penetrate small cracks in, e.g., building constructions. Fungal spore sizes are typically between 2 and 10 m (10, 36).…”
mentioning
confidence: 99%
“…In addition to spores, particles smaller than fungal spores are shown to be aerosolized from fungal cultures (16,28,37). These particles are referred to as fungal microparticles (measured sizes between 0.3 and 1.3 m in d a ) (37), fungal fragments (measured sizes between 0.3 and 1.5 m in optical diameter) (16), or fungal hyphal or conidial fragments (sizes not measured) (18) and can constitute a large part of bioaerosols in terms of numbers (16,18,36,52).…”
mentioning
confidence: 99%
“…Although bacterial communities and endotoxin concentrations have been reported in several studies (Gorny and Dutkiewicz 2002;Park et al, 2002;Herr et al, 2003;Oppliger et al, 2005;Rusca et al, 2008;Tendal and Madsen, 2011), only a few studies have evaluated their relationships with the types of land use (Mueller-Anneling et al, 2004;Madsen, 2006;Bowers et al, 2010;Tager et al, 2010;Woo et al, 2013). In a study designed to investigate the risk factors of childhood asthma, air samples were collected from several locations throughout Fresno, a city in central California, USA; the study revealed that the endotoxin concentrations varied among various geographical regions.…”
Section: Introductionmentioning
confidence: 99%